Dampak Optimasi Logistik Terhadap Penjualan UKM di Shopee Indonesia - Audita Fathana (Journal of Management and Bussines (JOMB), 2023)
This research aims to investigate the complex relationship between logistics optimization and sales performance among Small and Medium Enterprises (SMEs) operating on Shopee Indonesia. The research method uses a mixed methods approach, qualitative insights from interviews with SMEs provide an in-depth understanding of the challenges and positive impacts associated with logistics optimization. Qualitative insights from interviews highlight the challenges faced by SMEs, including financial constraints and lack of awareness, while also highlighting the positive impact of efficient logistics on customer satisfaction, loyalty and sales growth. Quantitative analysis strengthens these qualitative findings through statistically significant correlations. The adoption percentage in the area of logistics optimization indicates a proactive approach among SMEs in simplifying their operations. Financial impact data reflects the mixed results experienced by SMEs, with a significant percentage reporting significant improvements in profitability. The integration of qualitative and quantitative insights provides a holistic understanding of the challenges, strategies and outcomes associated with logistics optimization. Keywords: Sales Performance, Logistics Optimization, Shopee Indonesia